Evaluation of laterality in the snowboard basic position - Staniszewski, M.; Zybko, P.; Wiszomirska, I. (Human Movement, 2016)
Purpose. Snowboarding requires a lateral positioning of the body. Moreover, a person must continuously control their balance and use this in order to manoeuvre on the slope applying properly pressure on the lower limb closest to the nose of the board (the leading leg). The present study is an attempt to determine the interdependencies between side preference while snowboarding and laterality when performing other tasks. The dynamic stability in the neutral standing position, as well as in the lateral positions (left or right) was also evaluated.